Shifting the Focus to "Quality at Exit" - An Effective Approach to Improving the Business Environment at the Subnational Level - Binh, Le Duy (World Bank, Washington, DC, 2012)
Impact monitoring and quality assurance has always been an uphill task for donors, implementing agencies, and recipient agencies. In the last few decades, authors have witnessed the evolution of impact monitoring work with lots of new methodologies and concepts, resulting in thick documents that are sometimes difficult to digest. This paper does not aim to describe this evolution. Rather, it focuses on how the German Agency for Technical Cooperation (GTZ) Small and Medium Enterprise (SME) Development Program in Vietnam has adopted a new approach in impact monitoring and the challenges that authors are facing. It also describes first results and achievements, as well as key lessons drawn out of the process. Vietnam is a rising economy with discernible economic achievements in the last few years. Since 2000, the private sector in Vietnam has grown remarkably and is becoming increasingly important for the national economy. However, constraints facing the private sector are numerous, at both national and subnational level. The GTZ SME Development Program aims to improve the competitiveness of private SMEs in Vietnam by contributing to a favorable private sector policy framework. It also supports creating an enabling business and investment environment at the provincial level and fostering local economic development. Additionally, it helps enterprises to integrate into domestic and international value chains and supports the upgrading of business services.